Tindak Tutur Nasihat Bermuatan Nilai Integritas dalam Film Sepatu Dahlan - Sajidah Nur; Syafinaz Amalia Putri Sunardi; Muh. Asrandy Maharmawan; Martutik Martutik (Universitas Mulawarman, 2023)
The speech act of advice as a type of directive speech act is important to study. It is because speech acts of advice can influence speech partners in making decisions, determining views, and taking attitudes. One communication that contains speech acts of advice is the communication in the film Shoes Dahlan. Therefore, this research was conducted with two main, namely, to describe the functions of speech acts of advice and the value of integrity contained in speech acts of advice in the film Shoes Dahlan. The method used to achieve the two research objectives is a qualitative method. The speech act of advice contains the inculcation of the value of integrity. The research data was taken from a source in the film Shoes Dahlan. Documentation techniques are used in collecting data in this study. Documentation is done by watching the six films carefully. This study found (1) there were five functions of speech acts of advice, namely the functions of motivating, strengthening, suggesting, reminding, and advising (2) there are six character values in the speech act of advice, namely hard work, discipline, respect for others, humility, responsibility, and patience.